Evolutionary origin and function of NOX4-art, an arthropod specific NADPH oxidase - Ana Caroline Paiva Gandara; André Torres; Ana Cristina Bahia; Pedro L. Oliveira; Renata Schama (BMC Evolutionary Biology, 2017)
Abstract Background NADPH oxidases (NOX) are ROS producing enzymes that perform essential roles in cell physiology, including cell signaling and antimicrobial defense. This gene family is present in most eukaryotes, suggesting a common ancestor. To date, only a limited number of phylogenetic studies of metazoan NOXes have been performed, with few arthropod genes. In arthropods, only NOX5 and DUOX genes have been found and a gene called NOXm was found in mosquitoes but its origin and function has not been examined. In this study, we analyzed the evolution of this gene family in arthropods. A thorough search of genomes and transcriptomes was performed enabling us to browse most branches of arthropod phylogeny. Results We have found that the subfamilies NOX5 and DUOX are present in all arthropod groups. We also show that a NOX gene, closely related to NOX4 and previously found only in mosquitoes (NOXm), can also be found in other taxonomic groups, leading us to rename it as NOX4-art. Although the accessory protein p22-phox, essential for NOX1-4 activation, was not found in any of the arthropods studied, NOX4-art of Aedes aegypti encodes an active protein that produces H2O2. Although NOX4-art has been lost in a number of arthropod lineages, it has all the domains and many signature residues and motifs necessary for ROS production and, when silenced, H2O2 production is considerably diminished in A. aegypti cells. Conclusions Combining all bioinformatic analyses and laboratory work we have reached interesting conclusions regarding arthropod NOX gene family evolution. NOX5 and DUOX are present in all arthropod lineages but it seems that a NOX2-like gene was lost in the ancestral lineage leading to Ecdysozoa. The NOX4-art gene originated from a NOX4-like ancestor and is functional. Although no p22-phox was observed in arthropods, there was no evidence of neo-functionalization and this gene probably produces H2O2 as in other metazoan NOX4 genes. Although functional and present in the genomes of many species, NOX4-art was lost in a number of arthropod lineages.